Performance prediction of working memory retention using event-related potential signal towards children - Mohd. Tumari, Siti Zubaidah (Penerbit UTM Press, 2016)
This study is to investigate the Event-Related Potentials (ERP) from the background of Electroencephalograph (EEG) signal for working memory retention by using visual stimuli. The proposed analysis of ERP signal is to predict the performance of working memory retention for various frequency bands such as gamma, beta, alpha, theta and delta. This study is intended to process the EEG data into ERP data and analyze the ERP signal based on power spectrum density. This method is applied to data of normal children with age between 7 to 12 years old. Result showed that alpha power band increases during working memory retention towards visual stimuli compared to the other frequency band. 9 years old has the highest amplitude alpha power compared to the other group of age. Therefore, the alpha power band at the prefrontal cortex will be used for the next analysis of the working memory retention.